CHARACTERISTICS OF FEMALE GENITO-PELVIC PAIN-PENETRATION DISORDERS IN UROLOGY PATIENTS - Zamzami, Zuhirman; Afdal; Jaya, Indra; Yashar, M Adan; Pitoyo, Joko; Nur Azizi, Rizka (Indonesian Journal of Urology, 2025)
Objective: This study aims to identify the characteristics of GPPPD in urologic patients. Material & Methods: The research design used descriptive cross-sectional study conducted at urology clinic patients of Arifin Achmad Hospital, Pekanbaru, Riau Province in October 2021 to January 2022 The patients were interviewed based on validated questionaire. The data collected were urology diseases and disorders, age, symptoms, risk factors of biology, interpersonal, psychological, socio-cultural, sexual satisfaction. The study had been approved by ethical committee of Medical Faculty, Riau University. Univariate analysis were used. Results: There were 22 patients in the study with most urology disease were urinary tract infection (54.5%), while the most common age group was 41-60 years(77.3%) and the common risk factors were biological (41%), psychological (13.6%) and socio-cultural ones (100%). Conclusion: The characteristics of GPPPD in urologic patients were mostly with UTI, age group of 41-60 years and socio-cultural factors. Keywords: GPPPD, urology, urinary tract infection.